Impact of Gender in Renal Cell Carcinoma: The Relationship of FABP7 and BRN2 Expression with Overall Survival - Cheng Tan; Tatsuya Takayama; Naohisa Takaoka; Hiromi Fujita; Miki Miyazaki; Takayuki Sugiyama; Seiichiro Ozono (Clinical Medicine Insights: Oncology, 2014)
Objective To investigate the relationship between gender differences in fatty acid-binding protein7 (FABP7) and BRN2 (POU class 3 homeobox 2) expression in renal cell carcinoma (RCC) and the prognosis of patients with RCC. Materials and Methods immunohistochemical (IHC) staining as well as reverse transcription-polymerase chain reaction (RT-PCR) was performed in renal tissues from 103 patients (83 men, mean age = 63.6 years old; 20 women, mean age = 63.1 years old) underwent radical nephrectomy from January 1, 2001 through December 31, 2010. The probability of overall patient survival was estimated using the Kaplan–Meier method. Results FABP 7 mRNA expression was more frequent in men ( P = 0.07) while BRN2 protein expression was significantly more frequent in women ( P = 0.029). In particular, FABP7 was expressed in 100% of G1 renal cell carcinoma both in mRNA and protein levels. In women, FABP7 (–) and BRN2 (+) groups had a worse prognosis both in mRNA level ( P = 0.038) and protein level ( P = 0.058). BRN2 was expressed 100% of papillary RCC both in mRNA and protein levels. Conclusions Our results demonstrated that gender was a key factor in FABP7 and BRN2 expression in RCC, and the combination with FABP7 and BRN2 stratified by gender could be a new potential prognostic factor in patients with RCC.